Ferrite nanoparticles (MFe2O4 NPs) as magnetically recoverable supports for catalysis in organic synthesis. Issue 18 (16th September 2020) - Zhang, Xin; Aqeel Ashraf, Muhammad; Liu, Zhenling; Thai Pham, Binh; Zhang, Dangquan
Abstract: Heterogenization of organic and metallic catalysts with a solid support is an attractive and useful strategy to solve the separation and recovery problems of catalysts. During the last decade, magnetic nanoparticles (MNPs) in general ferrite nanoparticles (MFe2 O4 NPs) have emerged as a highly efficient support for catalysis, due to their simple fabrication, modification, and large surface area ratio. In this paper, we provide an overview of the utilization of organic and metallic molecules immobilized on magnetic ferrite nanoparticles (MFe2 O4 NPs) as attractive and efficient catalytic systems in wide variety of in organic reactions. Graphical Abstract: